Effectiveness of Psychodynamic Therapy on Marital Relationship Quality and Cognitive Emotion Regulation in Couples with Marital Conflicts - Araee, Ommolbanin; Mohammadzadeh Admolaee, Rajabali (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The aim of the present study was to determine the effectiveness of psychodynamic therapy on the quality of marital relationships and cognitive emotion regulation in couples experiencing marital conflicts. Methods and Materials: This research employed a quasi-experimental design with pretest-posttest and a control group. The statistical population consisted of couples with marital conflicts residing in Babol in 2023. From this population, 28 individuals (14 couples) were selected through convenience sampling and randomly assigned to either the experimental group (n = 14) or the control group (n = 14). Data were collected using standardized questionnaires measuring marital relationship quality and cognitive emotion regulation. The experimental group received psychodynamic therapy over 12 sessions (two 90-minute sessions per week), while the control group did not receive any treatment. Findings: The findings indicated that the posttest scores of both marital relationship quality and cognitive emotion regulation in the experimental group were significantly higher than the pretest scores. Conclusion: Therefore, psychodynamic therapy was found to be effective in improving marital relationship quality and cognitive emotion regulation among couples with marital conflicts.